Understanding Corruption with Perceived Corruption: The Understudied Effect of Corruption Tolerance. (4th March 2023) - Liu, Ting-An-Xu; Juang, Wen-Jong; Yu, Chilik
Abstract: Corruption diminishes the legitimacy of a government, and the extent of corruption perceived by the public reflects how transparent a government is to some extent. However, perceived corruption can vary across individuals because perceived corruption, which is a perception-based measurement of corruption, is sample-dependent and affected by culture, personal ethical standards, and specific contexts. Tolerance for corruption, which refers to an individual's willingness to tolerate unethical behaviors, is underdeveloped and understudied in the literature. With data collected with Random Digit Dialing technique in Taipei Taiwan, we conducted a parallel analysis to validate the scales to measure tolerance for corruption and examined its effect on perceived corruption controlling for institutional trust, satisfaction with government performance, and demographical variables. This study found partial evidence that tolerance for corruption with contextually fit items has a significant negative effect on perceived corruption with the survey data from Taipei, Taiwan, holding all the other variables constant. This result indicates that the higher the tolerance for corruption, the lower the perceived corruption. However, measuring tolerance for corruption is contextual. Scales for this construct should be further explored across cultures.